Fostering intergenerational education: An experiential learning program for medical students and older adults - Correia, Rebecca; Klea, Lindsay; Campbell, Graham; Costa, Andrew (Canadian Medical Education Journal, 2020)
Educational initiatives providing intergenerational, experiential learning opportunities can engage students of various education levels and disciplines. All persons can benefit from initiatives with older adults because our aging population suggests more of these interactions will occur across sectors. While students pursuing an education in health or medical fields are primarily identified as benefiting from intergenerational education to gain skills and knowledge to effectively care for the elderly, these teachings are invaluable regardless of one’s age, education, or career background. The program delivery and evaluation criteria can be adapted to assess competencies essential to different education or career paths.